Two‐year outcome of ventricular assist device via a modified left atrium to aorta approach in cardiac amyloidosis. (23rd June 2022) - Lim, Choon Pin; Lim, Yeong Phang; Lim, Chong Hee; Ong, Hean‐Yee; Tan, Daryl; Omar, Abdul Razakjr
Abstract: Cardiac amyloidosis is a debilitating disease associated with poor long‐term survival. Medical or palliative treatment is the usual course of therapy, but patients are often intolerant of conventional heart failure treatment. The current standard of care of sequential heart and bone marrow transplant is usually not feasible for ill or frail patients or in countries with limited organ donors or without transplant programmes. Left ventricular assist devices (LVAD) are not usually offered to these patients due to high peri‐operative risks and risks of suction events with the LVAD in a small left ventricle. We report the 2 year outcome and discuss the challenges faced in the management of our patient with end‐stage heart failure due to cardiac amyloidosis, who was successfully supported with an LVAD using a modified left atrium to aorta implantation technique.